Attitudes Concerning Antipsychotic Depot Medication in the German General Population: A Representative Telephone Survey. Issue 6 (December 2018) - Schmidt-Kraepelin, Christian; Engelke, Christina; Kahl, Kai G.; Cordes, Joachim
Abstract: Background: Treatment of schizophrenia with depot medication has advantages compared with oral medication, and among these include an improved compliance. Despite such advantages, prescription rates in many European countries are lower than 20%. The aim of this survey was to study the attitudes toward depot medication among the German general population. To the best of our knowledge, only selective samples have been investigated up until now. Methods: A representative sample of 754 people were interviewed via telephone by a professional market research and polling organization. The questionnaire queried demographic characteristics, experience with medication, and the treatment of mental disorders. Subjects' attitudes toward medication in general, long-term medication, and depot medication were surveyed. Results: Most (66.7%) of the subjects stated that they would be willing to receive depot medication. Subjects who experienced the treatment of mental disorders were more likely to be willing to receive depot medication. Among the reasons for not using depot medication, "fear of injection" (66.3%) and "more self-control when taking medication as tablets" (48.9%) were stated as the most frequent reasons. Conclusions: This study found a good acceptance of antipsychotic depot medication among the German general population in terms of willingness to receive such treatment. We argue that the clinical practitioners' assumptions that depot formulations would be refused by many patients are unsubstantiated.